2011
DOI: 10.1007/s00163-011-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive map-based system modeling for identifying interaction failure modes

Abstract: Past few decades have seen an upsurge in failure analysis techniques capable of dealing with reliability issues up front in the early stages of the product development process. Most of these approaches are centered on component-specific failures. However, with the advent of highly complex systems that derive functionalities from multiple physical phenomena domains, more emphasis is required on identifying failures arising due to various system interactions, which is largely absent in existing failure analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Yousefi S (with 9 papers) and Rezaee MJ (with 7 papers) have been among the most productive researchers in the field since 2017. Papageorgiou EI and Salmeron JL have 7 and 4 [79,116,73,144,145,74,132,11,98,159,115,164,124,143], Rezaee et al (2018b), [21], [86], [127], [102] 19…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yousefi S (with 9 papers) and Rezaee MJ (with 7 papers) have been among the most productive researchers in the field since 2017. Papageorgiou EI and Salmeron JL have 7 and 4 [79,116,73,144,145,74,132,11,98,159,115,164,124,143], Rezaee et al (2018b), [21], [86], [127], [102] 19…”
Section: Resultsmentioning
confidence: 99%
“…In this study, FCM was used to represent experts' knowledge of the target problem [90] provided a decision-making tool using FCM in the healthcare field to analyze meningitis risk in children and infants. Augustine et al [11] identified system interaction failure modes through FCM simulation and implemented it in an electric water heater system.…”
Section: Decision Makingmentioning
confidence: 99%
“…However, the qualitative considerations on risk and utility are based on classical systems engineering methodology and do not account for some complex features, for example, operational dependencies. Other authors include dependencies between variables in conceptual design (Nunez et al 2012), or in change propagation (Hamraz et al 2012), but only as a qualitative flow, or very simple model of binary or qualitative interdependencies (Augustine et al 2012), or with probabilistic assessments requiring many simulations (Clarkson et al 2004). SODA is a valid alternative to existing parametric models or to simulation-based models.…”
Section: Trade Space Exploration and Architecture Generationmentioning
confidence: 99%
“…However, in previous studies, the influence of failure modes was considered independently, and therefore, their proposed method was employed to overcome this weakness of FMEA. Augustine et al (2012) proposed a cognitive map model of physical systems for identifying interaction among failure modes. They argued that due to the causal nature of system interaction failures using cognitive maps in system modeling and simulation for failure analysis is greatly suitable and demonstrated the applicability of the proposed framework with an example of an electric water heater.…”
Section: Introductionmentioning
confidence: 99%